Beak coloration of starling (Sturnus unicolor) males depends on the length of their throat feathers. (13th May 2020) - Azcárate-García, Manuel; Ruiz-Rodríguez, Magdalena; Ruiz-Castellano, Cristina; Díaz-Lora, Silvia; Tomás, Gustavo; Martín-Vivaldi, Manuel; Soler, Juan José
Abstract: Within the context of complex sexual signaling, most research has focused on exploring the associations between several signals and/or their relationships with different proxies of individual quality. However, very few studies have focused on checking whether the expression of one signal is conditioned by the expression of the others. Here, by experimentally shortening the throat feathers of male spotless starlings ( Sturnus unicolor ), we evaluated the influence of this trait on the color expression of the beak base. In addition, we tested the relationship between these two sexually dimorphic characters with traits indicating individual qualities, such as body condition and color reflectance at the wavelength related to carotenes in the tip of the beak. Our results show that the coloration of the beak base in males, but not in females, is positively related to body condition and to the length of ornamental throat feathers. Moreover, the experimental shortening of throat feathers in males had a negative effect on the blue chroma intensity of their beak base 1 year after manipulation. These results support for the first time a causal link between the expression of two sexually dimorphic characters, which is essential to understand their functionality in a multiple signaling framework. Abstract : The use of signals to indicate individual quality is widespread in nature. However, although most species show more than one sexual signal, the relationships between them have almost never been studied experimentally. Here, we demonstrated that the experimental reduction of the throat feather length affected beak coloration of spotless starling males at the time of reproduction. Our results are the first experimental demonstration showing that two sexually selected traits are related under natural conditions.